PELIBATAN ORANG TUA DAN MASYARAKAT DALAM PEMBELAJARAN UNTUK MENINGKATKAN KESIAPAN LULUSAN MENGHADAPI DUNIA KERJA - Tomy Aditia; Yulius Mataputun; Petrus Irianto; Robert Masreng; Urip Wahyudin; Diki Kurniawan (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to analyze the involvement of parents and the community in vocational learning as an effort to enhance graduates’ readiness to enter the workforce at SMK Negeri 2 Tiom, Kabupaten Lanny Jaya. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving the principal, vocational teachers, parents, and community leaders. Data analysis was conducted thematically, referring to Joyce Epstein’s Parental Involvement Model, which includes the aspects of parenting, communicating, volunteering, learning at home, decision making, and collaborating with the community.The findings indicate that parental involvement occurs in the parenting aspect through everyday role modeling, such as discipline, responsibility, and work ethic, which are naturally instilled through family activities. Communication between the school and parents is carried out in a simple and contextual manner and is sufficiently effective in maintaining the continuity of values between home and school, although it is still constrained by language differences and limited access to communication technology. Parental participation in volunteering activities, assistance with learning at home, and involvement in school decision making remains situational and uneven; however, it still contributes to the development of students’ responsibility and independence.Collaboration among the school, community, and business or industrial sectors at SMK Negeri 2 Tiom relies primarily on local community potential due to limited access to formal industries in the mountainous region. The main supporting factors for involvement include strong social relationships and a shared sense of ownership of education, while the inhibiting factors consist of economic limitations, limited educational literacy, language differences, and minimal industrial networks. This study concludes that parental and community involvement is adaptive and contextual in nature and contributes significantly to the mental and social readiness of graduates to enter the workforce, although more sustainable strengthening strategies are still required.